Service Innovation for Route Permits and Public Transport Operations Permits through Si Pintar Solo at the Surakarta City Department of Transportation - Nina Septiani Safitri; Kristina Setyowati (Department of Public Administration, 2021)
Innovation is one way to restructure public services that are integrated with information technology. Starting from the existence of public transportation in the city of Surakarta that is no longer extending due to the revitalization of public transportation, the lack of network and route permits optimization and manual public transport permit services seem convoluted, slow and take a lot of time. The Surakarta City Department of Transportation created ‘Si Pintar Solo’ innovation, which is the the Solo Route and Operation Licensing Information System. This study aims to identify and understand the implementation of the Si Pintar Solo innovation by using the innovation theory according to Rogers (2003). This is a descriptive qualitative research, with primary data, such as interviews and secondary data from related documents. The sample selected by purposive sampling. The data validity used source triangulation. The data analyzed using interactive analysis. The results showed that the implementation of the Si Pintar Solo innovation described in each of the innovation attribute criteria, such as simplifying and accelerating services because it is supported by adequate facilities and infrastructure, according to community needs. Licensing is conducted online which does not require coming to the Surakarta City Department of Transportation office and is integrated with the e-Uji service. In addition, it could monitor the licensing process and the result of licensing data is stored in the database. However, there are obstacles, such as signal limitedness and the users’ quandary about innovations involving technology.